Public History and historical thinking. New methodological approaches to learn the Peninsular War - Moreno Vera, Juan Ramón (Hispania Nova, 2020)
This research analyses the learning outcomes of a group of Compulsory Secondary Education (CSE) students working on the Peninsular War on the basis of new methodological approaches, namely Historical Thinking, cooperation and Aronson’s Jigsaw. The study was carried out in L’Alluser Secondary School (Mutxamel, Alicante) with 75 students in Year 4 of CSE. Students were requested to fill a questionnaire, to be used as an assessment tool. It was then   analysed using the statistical IBM SPSS Statistics 24 package through the description of frequencies and percentages. The results show that (1) students prefer cooperative, rather than individual strategies in history education. (2) their capacity to do research using a variety of sources improves (3) this methodology helps students to improve their historical thinking abilities, including invisible topics (4).
Keywords: Public History; Teaching & Learning; Secondary Education; Teaching Methodology; Peninsular War